Święty Józef w nauczaniu św. Hieronima ze Strydonu - Łukaszczyk, Michał (Vox Patrum, 2025)
This article deals with Josephological issues in the writings of Jerome of Stridon. The monk from Bethlehem does not devote space to this saint directly in his reflections. Joseph occupies an important place in Christological discussions and in the defence of Mary's virginity. The author of the Vulgate also uses the example of Joseph in discussions concerning the superiority of a life of virginity over a life of marriage. It is possible to identify several themes related to St Joseph that Jerome addresses in his works: rejecting St Joseph's widowhood, emphasising his virginity, fighting for a true and not legendary representation of the figure of the Saviour's Protector, and justifying his remaining celibate due to his God-given mission. However, it must be said that the Author of the Vulgate touches on themes related to the Saviour's Protector in order to present a true Christology or to defend the Virgin Mary's virginity. It is worth emphasising that in the texts of Stridonian we can observe the beginnings of theological thought on the mission of St Joseph.